Policy Directives and Problem Mapping:Systematic Literature Review ofPublic Service Media Policy Studies - Rahayu, Rahayu; Yasa, Agne; Andina, Tri Kurnia Revul; Paramastri, Mira Ardhya (UI Scholars Hub, 2022)
This article aimed to map the themes of Public Service Media (PSM) studies, definitions, competition of interests, positions, and policy directives. Changes in the digital media sector have changed the characteristic of Public Service Broadcasting (PSB) into those of PSM. This change in character has led to a polemic on the relevance of PSB’s role and debates over media policies and regulations in a number of countries. Through a systematic study of literature, this research examined 62 journal articles related to media public service policies from 2003 to 2011. The search and selection of articles adapted the stages of the systematic literature study introduced by Lestón-Huerta, Goyanes, & Mazza (2021) who applied the “Prisma guideline” with various adjustments made in accordance to the study objectives. The results showed that most of the PSM policy studies still raised cases of PSM in Western countries, especially Europe. Most of the articles raised the setting of public broadcasting, media convergence, the internet, the economic crisis and political transition in discussing PSM policies. Most studies used a qualitative study approach. The findings identify a number of main themes in the PSM policy review, variations in the definition of PSM, three models of PSM’s position, and PSM policy directives which include the redefining of roles, funding, and management of PSM. This article was closed by conclusions and recommendations. Artikel ini bertujuan untuk memetakan tema studi Media Pelayanan Publik (PSM), definisi, persaingan kepentingan, posisi, dan arahan kebijakan. Perubahan di sektor media digital telah mengubah karakteristik Penyiaran Pelayanan Publik (PSB) menjadi PSM. Perubahan karakter ini telah menimbulkan polemik tentang relevansi peran PSB dan perdebatan tentang kebijakan dan regulasi media di sejumlah negara. Melalui kajian literatur yang sistematis, penelitian ini mengkaji 62 artikel jurnal terkait kebijakan pelayanan publik media dari tahun 2003 hingga 2011. Pencarian dan pemilihan artikel mengadaptasi tahapan studi literatur sistematis yang diperkenalkan oleh Lestón-Huerta, Goyanes, & Mazza (2021) yang menerapkan “pedoman Prisma” dengan beberapa penyesuaian yang dilakukan sesuai dengan tujuan studi. Hasil penelitian menunjukkan bahwa sebagian besar studi kebijakan PSM masih mengangkat kasus PSM di negara-negara Barat, khususnya Eropa. Sebagian besar artikel mengangkat latar penyiaran publik, konvergensi media, internet, krisis ekonomi dan transisi politik dalam membahas kebijakan PSM. Sebagian besar penelitian menggunakan pendekatan studi kualitatif. Temuan ini mengidentifikasi sejumlah tema utama dalam tinjauan kebijakan PSM, variasi dalam definisi PSM, tiga model posisi PSM, dan arahan kebijakan PSM yang meliputi pendefinisian ulang peran, pendanaan, dan manajemen PSM. Artikel ini ditutup oleh kesimpulan dan rekomendasi.